ANALISIS HUKUM TERHADAP KEGIATAN SEWA-MENYEWA SAFE DEPOSIT BOX - Elvira Fitriyani Pakpahan; Melinda Tarigan; Jessica Alana Putri Br. Ginting; Michelle Clarissa Yeoman; Nourma Dewi (LPPM Universitas Ekasakti Padang, 2023)
A safe deposit box service is a service formed by a bank to facilitate the storage of valuable assets, such as gold, securities, and other valuables. A safe deposit box is a box specially made of steel and placed in a strong and fire-resistant place to keep goods safe and provide a sense of security for stored goods. Safe deposit box services come with safe deposit boxes that have a high level of protection. This research, using normative legal research methods and secondary data sources, aims to find out how problems often arise in safety box rental activities and provide legal protection for customers who use safety boxes based on Law No. 8 of 1999. Problems that often occur in safe deposit box rental activities cause a lot of trouble for the community, so protection is needed for consumers who feel they have been harmed due to the negligence of the bank or the consumers themselves. As regulated in Article 4 of the Consumer Protection Act, consumers are entitled to comfort, security, and safety when consuming goods and services. To attract consumers, it requires a sense of public trust in the service manager so that consumers feel safe using these services.